Local body shape control of an articulated mobile robot and an application for recovery from a stuck state. (19th May 2022) - Nakajima, Mizuki; Fukumura, Shinnosuke; Tanaka, Kazuo; Tanaka, Motoyasu
Abstract : This paper proposes a method for an articulated mobile robot to change its local body shape in a complex environment. By coexisting a heuristic approach which is easy to design a motion in a complex three-dimensional environment and a model-based approach which can utilize the redundancy of the robot, the robot achieves propulsion in a complex environment and the local body shape control simultaneously. A part of the robot's body shape is changed based on a kinematic model, whereas the rest of it is controlled to follow the original shape or maintain its original position based on a heuristic method. As an application of the proposed method, the recovery motion from a stuck state is proposed. The robot is recovered from a stuck state by controlling the part of the robot that is in collision with an obstacle to move it away from the obstacle. The effectiveness of the proposed method is verified by experiments on an actual robot. GRAPHICAL ABSTRACT: UF0001